Biological profile of FCE 24517, a novel benzoyl mustard analogue of distamycin A. - Pezzoni, G. (Nature Publishing Group, 1991)
FCE 24157 (chemically (beta-[1-methyl-4-(1-methyl-4--[1-methyl-4-(4-N,N- bis(2-chloroethyl) amino-benzene-1-carboxy-amido) pyrrole-2-carboxiamido]pyrrole-2-carboxyamido)pyrrole-2-c arboxyamido]) propionamidine, hydrochloride) is a distamycin A (Dista A) derivative bearing a benzoyl mustard moiety instead of the formyl group at the N-terminal. Contrary to Dista A, FCE 24517 has been found to display potent cytotoxic activity on human and murine tumour cell lines. The compound maintains activity on melphalan (L-PAM)-resistant cells, whereas cross-resistance is observed on doxorubicin-(DX)-resistant cells. In vivo, FCE 24517 was found to possess evident antineoplastic activity on a series of murine transplanted solid tumours and human tumour xenografts. The following neoplasms were in fact found to be sensitive to FCE 24517 treatment: M14 human melanoma xenograft, N592 human small cell lung carcinoma, MTV murine mammary carcinoma, Colon 38 murine carcinoma, PO2 murine pancreatic carcinoma and M5076 murine reticulosarcoma. Lower effectiveness was observed against the murine P388 and Gross leukaemia, Lewis lung murine carcinoma, LoVo human colon carcinoma xenografts and A459 human lung adenocarcinoma. Against the murine L1210 leukaemia, FCE 24517 displayed a clear activity only when the tumour was transplanted i.p. and treatment was given i.p., whereas only marginal activity was seen against this leukaemia if transplanted i.v. and the drug was given i.v. As true also in vitro, FCE 24517 was effective against i.p. implanted L1210 leukaemia resistant to L-PAM. The mode(s) of action of this new compound is under active investigation.